Correlation Among Dividend Policy and Market Value of Equity In Banking Industry: A Residual Income Approach - Fadila, Ardhiani; Nugraheni, Siwi; Utami, Kery (Universitas Negeri Yogyakarta, 2023)
ABSTRACTThis research aims to examine the correlation between dividend payment and the market value of equity of banking firms in the Indonesia Stock Exchange-listed company. The sample includes firms focused on the banking sector period between 2011 to 2020. This study employs the residual income approach based on Ohlson's (1995) valuation model. The models are tested using panel regression analysis. Moreover, additional tests are used to ensure the main results. The finding shows that dividend payment has an insignificant effect on the market value of equity. The analysis states that the use of Ohlson's (1995) model and the firm's book value are statistically significant factors in determining the market value of equity. The study suggests that the dividend irrelevance hypothesis is valid in the case of banking firms on IDX. This paper encourages empirical evidence about the relationship between dividend payment and market value on Indonesia Stock Exchange, more importantly, in the banking firms.Keywords: Dividend Policy, Market Value, Residual IncomeABSTRAKTujuan penelitian ini untuk mengetahui korelasi antara pembayaran dividen dan nilai pasar saham pada perusahaan perbankan di Bursa Efek Indonesia. Sampel penelitian ini berfokus pada perusahaan perbankan selama periode 2011 sampai 2020. Penelitian ini menggunakan pendekatan residual income oleh model valuasi Ohlson's (1995). Model penelitian menggunakan analsis regresi panel. Selanjutnya, pengujian tambahan dilakukan untuk memastikan hasil pengujian utama. Temuan penelitian menunjukan bahwa pembayaran dividen tidak memiliki pengaruh terhadap nilai pasar saham. Hasil analisis menyatakan model Ohlson's (1995) dan nilai buku perusahaan secara statistik berpengaruh terhadap faktor penentu nilai pasar saham. Penelitian ini membuktikan teori ketidakrelevanan dividen berlaku dalam kasus perusahaan perbankan di BEI. Studi ini mendorong bukti empiris mengenai hubungan antara pembayaran dividen dan nilai pasar di BEI, khususnya pada perusahaan bank.Kata Kunci: Kebijakan Dividen, Laba Sisa, Nilai Pasar